City Branding Kendal: Strategi Pencitraan Daerah melalui Logo dan Tagline - Ismiati, Dwi; Rachman, Anung (Research and Development Agency Ministry of Home Affairs, 2023)
This study aims to find and describe the image of the area displayed through the visual elements contained in the Kendal reliable logo. City branding is one of the phenomena of the 21st century, which is a strategic effort for regions to increase competitiveness in global competition. Several cities or regencies in Indonesia have strong branding because they are made to follow the identity of the city that is formed. This study uses a qualitative method with logo and tagline theory to reveal the image displayed through its visual elements. Based on the observations and reviews of the logo and the tagline of the Kendal Handal logo, it was found that the elements of a good logo have been completed in Kendal City branding. Let's look back at the history of the Kendal tree, which is the origin of the name Kendal. The symbols in each of its elements contain the meaning of local wisdom, including geography, history, and culture. The regional image displayed from the logo's shape is not something static, and it will, of course, change according to its conditions. The Kendal Handal logo is part of the existing dynamics and represents the geographical, historical, and cultural conditions of each era.